(untitled) (European Journal of Health Research, 2022)
A topic of interest about prostitution research is the assessment of beliefs or attitudes related to. The Levin and Peled (2011) scale of Attitudes Toward Prostitutes and Prostitution is an innovative instrument with a quantitative methodology approach. Our aim will be to test the preliminary psychometric properties of this scale in Spanish population. Our sample included 357 students from the Miguel Hernández University. Most of them (74.8%; n = 267) are women and the rest are men (n = 90; 25.2%). The mean age was 20.8 years (SD: ± 4.6). The scale of Levin y Peled (2011) was culturally adapted by the research team and it was administered to selected sample. We analyze the internal consistency and construct validity. The Total Scale, Attitudes towards Prostitution Scale, and Election-Victim Prostitution subscale, showed internal consistency ≥.80. The Kaiser-Meyer-Olkin test was ≥. 80 and Bartlett test was significant (p = .000) were satisfactory scores for 2 or 4 factor models. We could not get any model to reproduce the same structure of original scale. The item analysis showed some item-total correlations <.20 that suggest to review them. As a conclusion, the authors support both models for 2 or 4 factors represent the scale in a coherent way with the theoretical framework.